Bibliotheca topographica et genealogica belgica : livres et manuscrits anciens ... de la collection Michel Wittock - Wittock, Michel; Speeckaert, Eric (Bruxelles : Eric Speeckaert, 1996)
Number of parcels: 286
Keywords: Boekgeschiedenis; Geodesie Cartografie; Genealogie Heraldiek; Veilingcatalogus